Plate IV: Hands of nine different mammals - Haeckel, Ernst (Natürliche Schöpfungsgeschichte: Gemeinverständliche Wissenschaftliche Vorträge über die Entwickelungslehre, 1872)
Plate illustrates the skeletal structures of the hands of nine different mammals: 1: man, 2: gorilla, 3: orangutan, 4: dog, 5: seal, 6: dolphin, 7: bat, 8: mole, and 9: platypus. This plate can be found in Ernst Haeckel's Natürliche Schöpfungsgeschichte: Gemeinverständliche Wissenschaftliche Vorträge über die Entwickelungslehre, or The History of Creation: Or the Development of the Earth and Its Inhabitants by the Action of Natural Causes.
Keywords: Evolution; Heredity; Human beings--Origin